Ragam Tema Historiografi Islam Sufistik Klasik di Indonesia - Fikri Surya Pratama (Jurnal Tamaddun, 2022)
This article aims to explain the various themes of classical Indonesian Sufistic scholars, where the writing of these classical Islamic texts was greatly influenced by the complexity of the life of Muslims in Indonesia during the classical period. This research is qualitative with historical research method. The source collection technique used is library research by searching for books, journal articles that discuss the following themes and direct tracing of Sufistic classical Islamic texts on the British Library website. Then followed by source criticism or selection of sources to be used, data analysis in the form of content analysis of the manuscript, finally historiography. The results of the study show that the various themes of classical Sufistic Islamic historigraphy in Indonesia show how the process of spreading and learning tarekat in the archipelago is not monotonous in the study of Sufism alone, but also includes studies related to everyday people's lives, starting with learning stories from the past. In the past, learning Arabic, combining traditional medicinal techniques with readings and prayers in the guidance of the Al-Qur'an Hadith, until reaching the problem of traditional community legal units, such as the inclusion of Islamic elements in the Minangkabau Customary Law. The local wisdom of the texts by Sufistic scholars, in this case, of course includes a very wide variety of things such as religious traditions, the diversity of understandings of Islamic content and various options for solutions in an effort to solve traditional problems and the culture of everyday people and so on, both both textual and contextual.